Probabilities of evoked and spontaneous synaptic transmission at individual active zones: Lessons from Drosophila - Bykhovskaia, Maria (Frontiers in Molecular Neuroscience, 2023)
Nerve terminals release neuronal transmitters at morphological specializations known as active zones (AZs). Synaptic vesicle fusion at individual AZs is probabilistic, and this property is fundamental for the neuronal information transfer. Until recently, a lack of appropriate tools limited the studies of stochastic properties of neuronal secretion at individual AZs. However, Drosophila transgenic lines that express postsynaptically tethered Ca2+ sensor GCaMP enabled the visualization of single exocytic event at individual AZs. The present mini-review discusses how this powerful approach enables the investigation of the evoked and spontaneous transmission at single AZs and promotes the understanding of the properties of both release components.